Effects of fine particulate matter air pollution on survival of Heliconius ethilla (Godart, 1819) - A. M. M. Charpinel; J. C. Féres; F. C. C. Barreto (Scientific Reports)
Abstract Human activities affect natural ecosystems worldwide and can generate negative effects on insect species such as growth inhibition, developmental abnormalities and reduction of reproductive and survival rates. Our study focused on fine particulate matter, a pollutant known to cause mechanical obstruction, heavy metal intoxication, and stress in Lepidoptera larvae. Heliconius ethilla (Lepidoptera: Nymphalidae) is a Heliconiinae found in the southeastern region of Brazil. We started our study with 3255 eggs, from which 69 stage 3 larvae were randomly separated as the treatment group. The larvae were fed with Passiflora edulis leaves and the SPM was added before being offered to the treatment group in an increasing concentration according to the age of the larvae and the leaf, simulating the gradual deposition of SPM in the environment. Our results demonstrate that Sedimentable Particulate Matter negatively impacted mortality rates, pupal weight, and body size. The results strongly indicate that the presence of SPM negatively impacts the survival, development and potentially the reproductive success of H. ethilla. A reduction in the population size and a consequent decrease in the chances of long-term survival of the species can be expected.